Begonia hanhhoae (Sect. Jackia), a new species of Begoniaceae from the South Central Coast region, Vietnam - Tran, Thi Thuy Nhan; Nguyen, van Canh; Nguyen, Thi Hoa; Averyanov, Leonid V.; Truong, Ba Vuong; Nguyen, Quoc Bao; Nguyen, van Khuong; Lin, Che Wei (Phytotaxa, 2026)
Begonia hanhhoae, a new species from Khanh Hoa Province, Ninh Hoa District, South Central Coast region, Vietnam, is described and illustrated. It resembles B. aspersa from northern Vietnam but differs in having broadly ovate to suborbicular leaves (vs. reniform) with a slightly waxy adaxial surface (vs. velvety), inflorescence with up to 13 flowers (vs. up to 5), actinomorphic androecium (vs. zygomorphic), and pistillate flowers that are subsessile or borne on very short pedicels up to 1.5 mm long (vs. 4–12 mm). According to the IUCN criteria, it has been tentatively assessed as Endangered (EN).